Memory enhancement in rats by soybean and tempeh extracts is associated with improved cholinergic and reduced neuroinflammatory activities - Alia Hamad; Vasudevan Mani; Kalavathy Ramasamy; Lim, Siong Meng; Abu Bakar Abdul Majeed (Penerbit Universiti Kebangsaan Malaysia, 2016)
The continued progression of neurodegeneration may result in dementia. The present study compared the neuroprotective activities between soybean and tempeh extracts in rats. The extracts were administered orally at 10, 20 and 40 mg/kg for 15 days. Radial arm maze and elevated plus maze served as exteroceptive behavioural models for memory measuring. Brain cholinergic activities (acetylcholine and acetylcholinesterase) and neuroinflammatory related cytokines interleukin 1β and interleukin-10 were also tested. Soybean and tempeh extracts significantly improved memory, but overall 40 mg/kg tempeh showed better improvement (p<0.05). The tempeh extracts at 20 and 40 mg/kg exhibited a significant (p<0.05) increase and decrease in the level of acetylcholine and acetylcholinesterase activities, respectively. Tempeh extract (40 mg/kg) resulted in greater reduction (p<0.05) of inflammation than soybean extract. Altogether, tempeh extract may be beneficial in the management and prevention of dementia and Alzheimer’s disease.